Aspects of nonrelativistic strong gravity - Hamamcı, Efe. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
We carry out the leading order (LO) large c expansion to GR in the presence of odd powers with the tools provided by Newton-Cartan (NC) gravity. As a result, a set of di eomorphism invariant LO equations are found. The odd power term is shown to be U(1) vector eld that appears in the equations through its eld strength. We nally show that the LO equations covers the stationary sector of GR entirely where the rotational degrees of freedom are provided by the U(1) eld.
Keywords: Gravity.